Markovnikov versus anti‐Markovnikov addition and C–H activation: Pd–Cu synergistic catalysis. (22nd October 2020) - Ullah, Zakir; Thomas, Renjith
Abstract : Copper‐ and palladium‐mediated transmetalation and coupling reactions are the backbone to several synthetic methodologies in organic chemistry for C–C bond formation. Computer‐aided simulations using density functional theory (DFT) (B3LYP‐D3 functional with 6‐31G** and effective core potential (ECP)‐LACVP** for heavy atoms for optimizations and cc‐pVTZ(−f) and ECP‐LACV3P** for single‐point calculations) was used to shed light on the probable mechanism of a novel synergistic Cu/Pd catalysts for the coupling of alkene, (Bpin)2 (where, pin = pinacolate), and vinyl‐ or aryl‐halogenated analogues. Every single conceivable pathway was carefully contemplated, and the base minimum energy pathway was found effectively. The copper‐catalyzed nucleophilic generation yields anti‐Markovnikov product using styrene as an alkene. This study affirms quantitatively and accurately how the reaction proceeds and at which steps of the synergistic catalysis the demand of the transmetalation and nucleophile formation for the C–C coupling using phosphine ligands arise. We conclude that the E and Z selectivity depends on the stereochemistry of the substrates used. Abstract : The copper‐catalyzed nucleophilic generation yields anti‐Markovnikov product using styrene as an alkene with Z isomer as enantioselective and diastereoselective product, and E and Z selectivity depends on the stereochemistry of the substrates used.